A cylindrical-core fibre optic oxygen sensor based on Pt (II) complexes immobilized in a polymer matrix - Chen, R; Farmery, A; Obeid, A; Hahn, C (2010)
The development of a cylindrical-core fiber optic oxygen sensor for fast measurement of oxygen partial pressure (pO 2) is described. The fibre sensing element is based on a cylindrical-core waveguide structure formed by a polymer sensing film that contains immobilized Pt (II) complexes. The performance of the fibre optic oxygen sensor was evaluated using luminescence intensity measurement. To determine accurately the response time of the oxygen sensor, a test chamber was used to provide rapid changes in the partial pressure of oxygen. The result showed that the time response of this cylindrical-core fibre based optic oxygen sensor can be less than 0.2 second. The details of the sensor chemistry, experimental system and the results are reported. © 2010 SPIE.